One-pot synthesis of PdZnO/C by microwave sintering method as an efficient electro catalyst for ethanol oxidation reaction. (8th March 2019) - Zhang, Zejie; Zhou, Debi; Wu, Xuewen; Bao, Xinjun; Liao, Jingjing; Zhang, Fangfang
Abstract: The PdZnO/C catalytic material for ethanol oxidation reaction is prepared by microwave heating-glycol reduction method. PdZnO is well polymerized and dispersed on XC72. The results demonstrate that PdZnO/C has better electro catalytic activity and stability for ethanol oxidation reaction than Pd/C at room temperature. ZnO/C shows no catalysis for ethanol oxidation. The oxidation peak potential of PdZnO/C electrode is shifted negatively to 0.21 V. The current density of PdZnO/C electrode is 145 mA cm −2, while that of the Pd/C electrode is 60 mA cm −2 . Moreover, single cell discharge test shows that discharge voltage of the PdZnO/C electrode reaches to 0.41 V at 30 mA cm −2 . In summary, ZnO as a co-catalyst significantly improves the activity of PdZnO/C catalyst for ethanol oxidation reaction. Highlights: The PdZnO/C catalyst for EOR was prepared by microwave heating-glycol method. The particle size of Pd is about 7 nm and the particles have good dispersion. Zinc oxide could increase the reaction kinetics of Pd/C as a co-catalyst for EOR. The EOR performance of the PdZnO/C electrode decreases slowly. The discharge voltage of the PdZnO/C cell reaches 0.41 V at 30 mA cm −2 .